Implementation of the Policy on Providing Regional Grant Assistance to Community Organizations at the National Unity and Politics Agency of Gorontalo Province - Bahi, Ronald; Abdussamad, Zuchri; Djafar, Lucyane (International Journal Papier Public Review, 2025)
The study aims to analyze and describe implementation of the policy of providing grant assistance to community organizations at the National Unity and Politics Agency of Gorontalo Province,) the determining factors for the success of the policy of providing grant assistance to community organizations at the National Unity and Politics Agency of Gorontalo Province. The research approach uses a qualitative method with a descriptive research method and the research procedure is carried out by observation and interviews with informants. The data analysis technique used is the interactive analysis of the miles and huberman model. The results of the study indicate that the implementation of the policy of providing regional grant assistance to community organizations at the National Unity and Politics Agency of Gorontalo Province has been running quite well. In terms of budgeting, the allocation of grant funds has been well planned. At the implementation and administration stages, the mechanism for disbursing grant funds has been running quite smoothly, the success of the implementation of the policy of providing regional grant assistance to community organizations is greatly influenced by various factors such as communication, which ensures that there is an understanding between the government and community organizations regarding the procedures and criteria for submitting grants. A proactive attitude and concern for the needs of community organizations will speed up the process. An efficient and flexible bureaucratic structure facilitates coordination between agencies, reduces administrative barriers, and accelerates the disbursement of funds.